Cost analysis of breast cancer: a comparison between private and public hospitals in Iran - Abolhasan Afkar; Habib Jalilian; Abolghasem Pourreza; Habibeh Mir; Abdolhosein Emami Sigaroudi; Somayeh Heydari (BMC, 2021)
Abstract Backgrounds Breast cancer is the most prevalent cancer among women. Breast cancer imposes a considerable economic burden on the health system. This study aimed to compare the cost of breast cancer among patients who referred to private and public hospitals in Iran (2017). Methods This was a prevalence-based cost of illness study. A total of 179 patients were selected from private and public hospitals using the census method. The researcher-constructed checklist was used for data collection. Data were analyzed using SPSS software version 22. Results The estimated total mean (SD) direct cost of patients who referred to the private hospital and the public hospital was $10,050 (19,480) and $3960 (6780), respectively. Further, the total mean indirect cost of patients who referred to the private hospital was lower than those referring to the public hospital at $1870 (15 % of total costs) and $22,350 (85 % of total costs), respectively. These differences were statistically significant (P < 0.05). Conclusions Breast cancer imposes a substantial cost on patients, health insurance organizations and the whole society in Iran. Therefore, the adoption of effective measures for the prevention and early diagnosis of breast cancer is urgently needed.